Efforts to Reduce Organic Matter In Shrimp Aquaculture Wastewater With Various Bacterial Consortium Trademarks - Diana Arfiati; Shofiyatul lailiyah; Rizky Kusma Pratiwi; Dini Alvateha; Fidhiyah Dita Dahria Aisyah; Karina Farkha Dina (Airlangga University, 2021)
Shrimp aquaculture wastewater after the end of the rearing period has a high total organic matter (TOM) content of up to 87.74 mg/L. If the wastewater is disposed of directly without any efforts to reduce or treatment, it will disturb public waters ecosystem because of the high organic matter. The aim of this study was to determine the rate of reduce of organic matter in pond aquaculture waste. The study was carried out in January 2021. Pond wastewater samples were taken from the Tambak at the end of the maintenance period (120 days of maintenance). The trademarks of the bacterial consortium are EM4, Bio HS, BIO Prisma, Starbio plus, BIO2000, and Biolet. The experimental research was arranged in a completely randomized design with 6 treatments and 4 replications. Each treatment was filled with 2 liters of wastewater plus 6 ml of a liquid bacterial consortium. As for the solid bacterial consortium, 1 gram/L was added. Measurements of total organic matter, temperature, pH, dissolved oxygen, salinity and carbon dioxide were carried out every 24 hours for 72 hours of observation. The results showed that during 72 hours of immersion the highest percent reduction in organic matter was in treatment E (BIO 2000) of 95% (87.74 mg/L to 4.11 mg/L). The lowest percentage decrease was in treatment D (Starbio plus) of 83.4% (87.74 mg/L to 14.54 mg/L). However, in general 6 types of bacterial consortium trademarks can degrade organic matter. The levels of temperature, pH, dissolved oxygen and salinity are in optimum conditions, while carbon dioxide exceeds the threshold caused by the high activity of overhauling organic matter by bacteria. The conclusion was obtained that the trademark of the bacterial consortium BIO2000 was the most effective in reducing organic matter for 72 hours. Keyword : Shirmp wastewater, Tambak, Bioremediation, Organic Matter, Microorganis